“Stromal cells in prostate cancer pathobiology: friends or foes?” - Filippo Pederzoli; Massimiliano Raffo; Hubert Pakula; Francesco Ravera; Pier Vitale Nuzzo; Massimo Loda (2022)
Abstract The genomic, epigenetic and metabolic determinants of prostate cancer pathobiology have been extensively studied in epithelial cancer cells. However, malignant cells constantly interact with the surrounding environment—the so-called tumour microenvironment (TME)—which may influence tumour cells to proliferate and invade or to starve and die. In that regard, stromal cells—including fibroblasts, smooth muscle cells and vasculature-associated cells—constitute an essential fraction of the prostate cancer TME. However, they have been largely overlooked compared to other cell types (i.e. immune cells). Indeed, their importance in prostate physiology starts at organogenesis, as the soon-to-be prostate stroma determines embryonal epithelial cells to commit toward prostatic differentiation. Later in life, the appearance of a reactive stroma is linked to the malignant transformation of epithelial cells and cancer progression. In this Review, we discuss the main mesenchymal cell populations of the prostate stroma, highlighting their dynamic role in the transition of the healthy prostate epithelium to cancer. A thorough understanding of those populations, their phenotypes and their transcriptional programs may improve our understanding of prostate cancer pathobiology and may help to exploit prostate stroma as a biomarker of patient stratification and as a therapeutic target.